A Biologically Muscle‐Inspired Polyurethane with Super‐Tough, Thermal Reparable and Self‐Healing Capabilities for Stretchable Electronics - Ying, Wu Bin; Wang, Guyue; Kong, Zhengyang; Yao, Chen Kai; Wang, Yubin; Hu, Han; Li, Fenglong; Chen, Chao; Tian, Ying; Zhang, Jiawei; Zhang, Ruoyu; Zhu, Jin (Advanced functional materials, 2021)
Polymeric elastomers play an increasingly important role in the development of stretchable electronics. A highly demanded elastic matrix is preferred to own not only excellent mechanical properties, but also additional features like high toughness and fast self‐healing. Here, a polyurethane (DA‐PU) is synthesized with donor and acceptor groups alternately distributed along the main chain to achieve both intra‐chain and inter‐chain donor‐acceptor self‐assembly, which endow the polyurethane with toughness, self‐healing, and, more interestingly, thermal repair, like human muscle. In detail, DA‐PU exhibits an amazing mechanical performance with elongation at break of 1900% and toughness of 175.9 MJ m−3. Moreover, it shows remarkable anti‐fatigue and anti‐stress relaxation properties as manifested by cyclic tensile and stress relaxation tests, respectively. Even in case of large strain deformation or long‐time stretch, it can almost completely restore to original length by thermal repair at 60 °C in 60 s. The self‐healing speed of DA‐PU is gradually enhanced with the increasing temperature, and can be 1.0–6.15 µm min−1 from 60 to 80 °C. At last, a stretchable and self‐healable capacitive sensor is constructed and evaluated to prove that DA‐PU matrix can ensure the stability of electronics even after critical deformation and cut off. A highly desirable elastic matrix is preferred to own not only excellent mechanical properties, but also additional features high toughness and fast self‐healing. Here, a polyurethane is synthesized with donor and acceptor groups alternately distributed along the main chain to achieve both intra‐chain and inter‐chain donor‐acceptor self‐assembly, which endow the polyurethane with toughness, self‐healing, and thermal repair, like muscle.